Case report on tuberous sclerosis: a rare cause of seizure - Nilavan Prahalathan, Kathir; Sureshkumar, Sowmika; Subramani Reddy, Preethi Putti Reddy; Abdulla, Nawaf; Venkatesan, Divya; Ramasamy, Balakrishnan (International Journal of Research in Medical Sciences, 2022)
We report a case of tuberous sclerosis in a 19 years old teenage patient with generalized tonic-clonic seizure. MRI brain showed linear CSF filled structure with surrounding gliosis extending from the frontal horn of right lateral ventricle to the pial surface of right frontal lobe-postoperative change. Multiple small T2/ FLAIR hyper-intensities without diffusion restriction in bilateral frontal temporal parietal and left occipital lobes, predominantly involving the cortex and sub-cortical white matter and small focus of calcification in left parietal peri-ventricular white matter. He was treated with valproic acid, sodium valproate and levetiracetam and showed prompt improvement. Epilepsy in tuberous sclerosis complex is a group of genetic disorders manifesting in childhood. Secondary causes of tuberous sclerosis should be suspected when there is abrupt onset in adulthood. The case highlights an uncommon case of epilepsy in tuberous sclerosis in young adult patient.